2001
DOI: 10.1103/physreva.63.023413
|View full text |Cite
|
Sign up to set email alerts
|

Quantum slow motion

Abstract: We investigate the center-of-mass motion of cold atoms in a standing amplitude modulated laser field. We use a simple model to explain the momentum distribution of the atoms after any distinct number of modulation cycles. The atoms starting near a classical phase-space resonance move slower than we would expect classically. We explain this by showing that for a wave packet on the classical resonances we can replace the complicated dynamics in the quantum Liouville equation in phase space by its classical dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, if one assumes the mean of maximum and minimum momenta occupied by the region of regular motion (when positioned on the momentum axis) as a classical momentum approximation for the experimentally observed momentum peak, the classical resonance momenta are still significantly faster than the experimentally measured values. These results suggest a possible explanation in terms of the theory of quantum slow motion [44], but more rigorous and detailed investigation would be needed to confirm this. The theory of quantum slow motion shows that the complicated quantum dynamics of the atomic wavepacket on a classical resonance given by the quantum Liouville equation can be replaced by the wavepacket's (in fact, the corresponding classical probability distribution's) classical dynamics with a modified potential within certain limits.…”
Section: Experimental Resonance Momenta In the Bifurcation Sequence Amentioning
confidence: 81%
See 2 more Smart Citations
“…However, if one assumes the mean of maximum and minimum momenta occupied by the region of regular motion (when positioned on the momentum axis) as a classical momentum approximation for the experimentally observed momentum peak, the classical resonance momenta are still significantly faster than the experimentally measured values. These results suggest a possible explanation in terms of the theory of quantum slow motion [44], but more rigorous and detailed investigation would be needed to confirm this. The theory of quantum slow motion shows that the complicated quantum dynamics of the atomic wavepacket on a classical resonance given by the quantum Liouville equation can be replaced by the wavepacket's (in fact, the corresponding classical probability distribution's) classical dynamics with a modified potential within certain limits.…”
Section: Experimental Resonance Momenta In the Bifurcation Sequence Amentioning
confidence: 81%
“…For most tunnelling phenomena which have been observed in the past, for example α-particle decay, conservation of energy forbids the process classically. Furthermore, Hug and Milburn [44] showed that quantum mechanical velocity predictions for phase space resonances disagree by up to 20% with classical predictions in the atomoptics-driven pendulum. Experimental results which may possibly be linked to this phenomenon will be discussed in section 5.…”
Section: Rationale and Structurementioning
confidence: 99%
See 1 more Smart Citation
“…To date, we know of two kinds of quantum effects for this system. Firstly, the velocity of the resonances predicted in quantum and classical models differs significantly for values of large k. A velocity shift was predicted theoretically by Milburn et al in the theory of quantum slow motion [14].…”
Section: Introductionmentioning
confidence: 88%
“…The behaviour of such systems has provided important insights into the quantum-classical transition [7][8][9][10][11][12][13][14]: in particular, the period of the dynamical tunnelling is strongly affected by a number of subtle effects [11][12][13][14]. Dynamical tunnelling has mostly been studied in the single-particle regime [12,[15][16][17][18][19], and has been demonstrated experimentally with ultra-cold atoms in modulated optical lattice potentials [20,21]. Recently it has been shown in [14] that atomic interactions in trapped Bose-Einstein condensates (BECs) can have a detectable effect for experimentally realistic parameters.…”
mentioning
confidence: 99%